Hindu and Mohammedan Law - K, Thomas (Journal of Dharma, 1984)
William Markby Hindu and Mohammedan Law Inter-India Publishers, New Delhi, First Pub. 1906; Reprint 1977. Rs. 50/- pp. 172, Appendix, Index.